Effect of zinc oxide nanoparticle concentration coated on acrylic resin upon surface roughness and abrasion resistance - Yoga, I Gede Krisna Merta; Harsini, Harsini; Sunarintyas, Siti; Handajani, Juni; Nuryono, Nuryono; Irnawati, Dyah (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Acrylic resin is the material most often used as a base for dentures; however, acrylic resin has shortcomings in its biological properties as it does not have antimicrobial properties. ZnO is added to acrylic resin because of its antimicrobial properties. The aim of this research is to determine the effect of the concentration of ZnO nanoparticles as a heat polymerization acrylic resin coating on the coating’s resistance to abrasion. A total of 24 acrylic resin samples were made, each measuring 13 x 13 x 2 mm. The acrylic resin was coated with 3-(trimethoxysilyl)propyl methacrylate), then with ZnO nanoparticles with varying concentrations of 2.5%, 5%, and 7.5% in ethanol. ZnO nanoparticle coating was applied using the dip coating method. Subsequently, the samples were subjected to an initial roughness test, abrasion test, and final roughness test. The data obtained were analyzed using one-way ANOVA and LSD(0.05). The results showed that the mean change in roughness (μm) and standard deviation for groups I to IV were 0.11 ± 0.13, 0.08 ± 0.33, 0.1 ± 0.12, and 0.19 ± 0.15, respectively. The results of the one-way ANOVA test showed that there was no significant difference in the roughness after the abrasion test (p > 0.05). Thus, zinc oxide nanoparticles can reduce surface roughness and are resistant to surface abrasion.